An investigation of the impact of exchange rate movements on consumer prices in the Southern African Customs Union (SACU) - Teboho Mashao; Ireen Choga (Cogent Business & Management, 2023)
External shocks disrupt the effectiveness of the central bank in stabilising prices. Therefore, this study investigates the effect of exchange rate movement on consumer prices in the SACU region for the period from 1990 to 2021 (31 observations for each nation). To achieve this, panel auto-regression distributed lags (PARDL) and pooled group mean (PGM) estimation techniques were employed in this study. Variables used in this study include consumer price index, exchange rate, import prices, gross domestic product (GDP) and money supply. The results indicate that the exchange rate has significantly influenced consumer prices negatively in the SACU region in the long run. Furthermore, the effects of exchange rate on consumer prices are low and incomplete. This undermines the PPP theory, which asserts that local prices should change in the same direction as the exchange rate. Nonetheless, the long-run findings align with some empirical evidence within the region. The short-run effects of the exchange are mixed and only significant in Botswana. Moreover, consumer prices in the SACU region are influenced by GDP, money supply and exchange rate. Granger causality results indicate that there is a unidirectional relationship between consumer prices and exchange rate. The findings in this study have implications for monetary policy in the SACU region. The exchange rate is anti-inflationary. Inflated consumer prices are likely to have been influenced by internal forces. Therefore, it is imperative to reconsider monetary policy targets and how they may be reorganised to regulate the level of consumer prices in the SACU economies.
Keywords: 650; consumer prices; exchange rate; movements; PARDL; PMG; SACU